Chitosan-based buccal mucoadhesive patches to enhance the systemic bioavailability of tizanidine - Arpa, Muhammet Davut; Üstündağ Okur, Neslihan; Gök, Mehmet Koray; Özgümüş, Saadet; Cevher, Erdal (Elsevier B.V., 2023)
Tizanidine hydrochloride (TZN) is a muscle relaxant used to treat a variety of disorders such as painful muscle spasms and chronic spasticity. TZN has low oral bioavailability due to extensive first-pass metabolism and is used orally at a dose of 6–24 mg per day. In the present study, buccal patches were prepared by solvent casting method using chitosan glutamate (Chi-Glu) and novel chitosan azelate (Chi-Aze) which was synthesised in-house for the first time, to enhance the bioavailability of TZN by bypassing first-pass metabolism. The characterisation, mucoadhesion and drug release studies were performed. Chi-Aze patches retained their integrity longer in the buccal medium and showed higher ex vivo drug permeability compared to that prepared with Chi-Glu. In vivo studies revealed that buccal formulation fabricated with Chi-Aze (3%) showed approx 3 times more bioavailability than the orally administered commercial product. Results of the studies indicate that Chi-Aze, prepared by conjugation of chitosan and a fatty acid, the patch formulation is a promising buccal mucoadhesive system due to the physical stability in buccal medium, the good mucoadhesiveness and the high TZN bioavailability. Moreover, Chi-Aze patch might be an alternative to oral formulations of TZN to reduce the dose and frequency of drug administration.
Keywords: Azelaic Acid; Bioavailability; Buccal Patch; Chitosan; Mucoadhesion; Tizanidine